Cumulative sum analysis for evaluating learning curve of endoscopic lateral neck dissection - Zhen-Xin Chen; Xin-Ran Zhao; Jie-Min Deng; Ying Cao; Jing-Bao Chen; Feng-Shun Pang; Zhan-Hong Lin; Xiao-Bo Zhang; Bo Xu; You Qin (BMC Surgery)
Abstract Objectives Endoscopic lateral neck dissection (LND) can be a scarless procedure if a surgeon has performed a sufficient number of operations to become skilled at the techniques involved. Here, we examine the learning curve for a surgeon who performed 53 endoscopic LND procedures via chest approach. Methods Surgical outcomes for 53 patients with papillary thyroid carcinoma who underwent endoscopic LND via chest approach between February 2017 and November 2022 were retrospectively reviewed. The surgeon’s learning curve was evaluated using a cumulative sum graphic model (CUSUM). Results A CUSUM analysis was applied to 53 patients (10 males, 43 females) with a mean age of 41.4 y who underwent endoscopic LND via chest approach. The best model for the curve was determined to be a third-order polynomial equation as follows: CUSUMOT = − 0.007×patient number3-0.666×patient number2 + 55.721×patient number − 72.964. This equation has a high R2 value of 0.929. The peak operative time (OT) occurred at the 30th case. Consequently, the learning curve model was divided into two phases: phase 1 (1–30 cases) and phase 2 (31–53 cases). OT (307.9 ± 63.8 min vs. 232.4 ± 44.2 min, respectively; p < 0.001), blood loss (50 mL vs. 20 mL, respectively; p = 0.001), and complications (43.3% vs. 13.0%, respectively; p = 0.038) decreased significantly in phase 2 compared to phase 1. Conclusions The learning curve of endoscopic LND via chest approach was found to involve 30 cases. With greater experience, the surgery was completed with shorter OT and fewer complications. This approach may be an alternative for patients who desire cosmesis. Furthermore, the present data and experience insights regarding endoscopic LND via chest approach may help other surgeons to pass the learning phase more safely.